The Use of Print and Electronic Media in Health Promotion Learning: Literature Review - Astuti, Puji (Mandalika Journal of Medical and Health Studies, 2025)
The Fourth Industrial Revolution is a condition in the 21st century when there are massive changes in various fields through the combination of technologies. The education sector has also been exposed to the influence of technological digitalization which has brought positive and negative influences. Dalam dunia pendidikan, learning media is an inseparable part and it is an integration of the learning methods used. This study aims to describe the role of print media and electronic media in health promotion learning. The research method used was qualitative and data collection was carried out by literature study. Results of research on the use of media in the learning process can improve the quality and learning outcomes and is determined by the ability of the teacher to choose the media to be used. Some considerations that need to be made to choose media in learning are; consideration of students or goals, consideration of learning objectives, consideration of learning strategy, consideration of ability in designing and using media, consideration of cost, consideration of facilities and infrastructure, and consideration of efficiency and effectiveness. It is suggested that the promotion carried out is adjusted to the target, for which the health promotion carried out must pay attention to various situations/places/settings considering the level of health promotion targets, namely primary, secondary, and tertiary targets.